Activation of mirror neuron system during gait observation in sub-acute stroke patients and healthy persons. (February 2019) - Hioka, Akemi; Tada, Yoshiteru; Kitazato, Keiko; Kanematsu, Yasuhisa; Mizobuchi, Yoshifumi; Mure, Hideo; Shimada, Kenji; Okazaki, Toshiyuki; Korai, Masaaki; Akazawa, Naoki; Matsumoto, Yuki; Harada, Masafumi; et al.
Highlights: We investigated activation of mirror neuron system during gait observation. Participants were sub-acute stroke patients and healthy persons. Activation of the mirror neuron system was observed in those participants. Gait observation treatment may improve gait ability in sub-acute stroke patients. Abstract: The observation of walking improves gait ability in chronic stroke survivors. It has also been suggested that activation of the mirror neuron system contributes to this effect. However, activation of the mirror neuron system during gait observation has not yet been assessed in sub-acute stroke patients. The objective of this study was to clarify the activation of mirror neuron system during gait observation in sub-acute stroke patients and healthy persons. In this study, we sequentially enrolled five sub-acute stroke patients who had undergone gait training and nine healthy persons. We used fMRI to detect neuronal activation during gait observation. During the observation period in the stroke group, neural activity in the left inferior parietal lobule, right and left inferior frontal gyrus was significantly higher than during the rest period. In the healthy group, neural activity in the left inferior parietal lobule, left inferior frontal gyrus, left middle frontal gyrus, left superior temporal lobule and right and left middle temporal gyrus was significantly higher than during the rest period. The results indicate that the mirror neuron system was activated during gait observation in sub-acute stroke patients who had undergone gait training and also in healthy persons. Our findings suggest that gait observation treatment may provide a promising therapeutic strategy in sub-acute stroke patients who have experienced gait training.